Chemically crosslinked liquid crystalline poly(ionic liquid)s/halloysite nanotubes nanocomposite ionogels with superior ionic conductivity, high anisotropic conductivity and a high modulus. Issue 8 (11th February 2019) - Li, Hao; Feng, Zhiqiang; Zhao, Kang; Wang, Zihao; Liu, Jiahang; Liu, Jie; Song, Hongzan
Abstract : Highly anisotropic conductive poly(ionic liquid)s-based liquid crystalline nanocomposite ionogel with superior ionic conductivity and high modulus has been successfully fabricated. Abstract : A novel type of chemically crosslinked liquid crystalline nanocomposite ionogel electrolyte based on poly(ionic liquid) (PIL) with superior ionic conductivity and high anisotropic conductivity was designed and synthesized using the in situ photopolymerization of sheared soft ionogels containing charged halloysite nanotubes (HNTs) and ionic liquid monomers. The oriented structure was investigated using scanning electron microscopy (SEM) and small-angle X-ray scattering (SAXS). The chemically crosslinked backbone of the PIL and the addition of HNTs endowed the flexible ionogels with a combined very high modulus (up to 26.7 MPa) and mechanical strength (up to 4.4 MPa). Crucially, the obtained ionogels exhibited high mechanical stability even at temperatures up to 200 °C. Remarkably, in terms of the conductivities, the resulting pre-sheared ionogels displayed superior room temperature ionic conductivity (up to 6 mS cm −1 ) and a very high conductivity anisotropy ratio (up to 1600), owing to the alignment of the HNTs with oppositely charged surfaces and the high ionic conductivity of the polyelectrolyte PILs. Furthermore, flexible solid-state supercapacitor devices based on the high ion-conductive nanocomposite ionogels were fabricated, which demonstrated high and temperature-dependent specific capacitance, and remarkable cycling stability and flexible performance.